Molecular dynamics studies of liquids using a Beowulf computer - Mij, Probert (Contemporary physics, 2003)
Molecular dynamics is a popular methodology for investigating the properties of liquids. In this article, the historical development of the subject and its current status will be briefly reviewed. The different parallelisation strategies that are commonly used are discussed, highlighting their relative strengths and weaknesses. Particular attention is given to the software and hardware aspects of implementing these algorithms on the 'Beowulf class' of parallel computers. Finally, three different examples of parallel molecular dynamics studies on a Beowulf computer will be discussed, that are indicative of the range of potential applications.